EFEK PENGGUNAAN PUPUK DAUN BAYFOLAN DAN PUPUK SP-36 TERHADAP PERTUMBUHAN DAN HASIL TANAMAN MELON (Cucumis melo L.) VARIETAS ACTION 434 - Hamidah . (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2013)
Research purposes to determine the effect of foliar fertilizer and manure Bayfolan SP-36 on the growth and yield of melon. The experiment was conducted in the village of Muang Benanga In Lempake Village District North Samarinda, East Kalimantan, for 5 months starting from January to May 2011. The experiment was conducted in a randomized block design (RBD) with a 4x4 factorial experiment was repeated 3 times. The first factor is Bayfolan leaf manure (B) consisting of 4 levels of concentration, ie B0 (without fertilization), B1 (1.5 ml / L of water), B2 (3 ml / L of water). While the second factor is the SP-36 (S) consisting of 4 dose levels, ie S0 (without fertilization), S1 (450 Kg / Ha), S2 (900 Kg / Ha), S3 (1350 Kg / ha). Results of analysis of variance showed that the influence of leaf manure Bayfolan (B) was not significantly different for plant height ages 2 and 4 weeks after planting, the number of leaf age 2 weeks after planting, age of the plant during flowering, fruit weight and yield fruit crop per hectare, but significantly different to the number of leaf age 4 weeks after planting. Most likely the number of leaves found on the treatment concentration of 3 ml / L of water. Effect of SP-36 (S) was not significantly different for plant height ages 2 and 4 weeks after planting, the number of leaf age 2 and 4 weeks after planting, planting fruit weight, fruit set per hectare, but significantly different to the age of the plant during flowering. Fastest time of flowering plant age at treatment doses are 900 Kg / Ha. Interaction effect between leaf manure and fertilizer Bayfolan SP-36 does not give a real difference.